1
x>0,y>0
{x²+y²=5
{log(2)x+log(2)y=1⇒log(2)xy=1⇒xy=2⇒2xy=4
прибавим
x²+y²+2xy=9
(x+y)²=9
a)x+y=-3
x=-3-y
-3y-y²=2
y²+3y+2=0
y1+y2=-3 U y1*y2=2
y1=-2 не удов усл
у2=-1 не удов усл
б)x+y=3
x=3-y
3y-y²=2
y²-3y+2=0
y1+y2=3 U y1*y2=1
y1=1⇒x1=2
y2=2⇒x2=1
(2;1);(1;2)
2
x>0,y>0
{x²-y²=12
log(2)x-log(2)y1⇒log(2)(x/y)=1⇒x/y=2⇒x=2y
4y²-y²=12
3y²=12
y²=4
y1=-2 не удов усл
y2=2⇒x=4
(4;2)
3
x>0,y>0
{x²+y²=25
lgx+lgy=lg12⇒xy=12⇒2xy=24
x²+y²+2xy=49
(x+y)²=49
a)x+y=-7
x=-y-7
-y²-7y=12
y²+7y+12=0
y1+y2=-7 U y1*y2=12
y1=-3 не удов усл
y2=-4 не удов усл
б)x+y=7
x=7-y
7y-y²=12
y²-7y+12=0
y1+y2=7 U y1*y2=12
y1=3⇒x1=4
y2=4⇒x2=3
(4;3);(3;4)
4
x>0 y>0
{log(0,5)xy=-1⇒xy=2
{x=3+2y
3y+2y²-2=0
D=9+16=25
y1=(-3-5)/4=-2 не удов усл
у2=(-3+5)/4=0,5⇒х=4
(4;0,5)
2/3 <x <3 ≡ x ∈ (2/3; 3)
b) x≠-3 ; x≠2 ; x≠ 1,25
D(f) = (-∞; -3) U (-3; 1,25) U (1,25; 2) U (2; ∞)
1) x ∈ (-∞; -3) ⇒
(x+3) · (x-1,25) · (x- 2) ?
<0 ; <0 ; <0 <0 ⇒ верно
2) x ∈ (-3; 1,25) ⇒
>0 ; <0 ; <0 >0 ⇒ ne werno
3) x ∈ (1,25; 2)
>0 ; >0 ; <0 <0 ⇒ verno
4) x ∈ (2; ∞)
>0 ; >0 : >0 >0 ⇒ ne werno
ответ: x = (-∞; -3) U (2; ∞)